The Nature of Biomimicry: Toward a Novel Technological Culture. (September 2017) - Fisch, Michael
Biomimicry is a rising popular ecology movement and method that urges the derivation of innovative and environmentally sound design from organic systems. This essay explores the notion of nature in biomimicry as articulated by the movement's founder, Janine Benyus, and the nature of biomimicry as practiced by the Massachusetts Institute of Technology (MIT) media ecologist Neri Oxman. Benyus's approach, I show, promotes biomimicry as a science of nature in which nature is treated as a source for innovative design that can be emulated in technological apparatus. Such an approach is problematic, I argue, for its valorization of organic form, which results in both a rigid system of ethics demanding absolute separation of nature and technology. By contrast, Oxman's work, I show, pursues biomimicry as a technology of nature. In so doing, I argue, it mobilizes a neomaterialist style of interaction with organic materials that ultimately enjoins a radically different way of thinking nature, technology, and technoethics.